2009
DOI: 10.1007/s11104-008-9869-9
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between aluminum toxicity and manganese toxicity in soybean (Glycine max)

Abstract: Aluminum (Al) and manganese (Mn) toxicity are two main constraints to crop production in some acid soils. In the present study, hydroponic experiments were conducted to investigate the phytoxicity caused by the metals Al and Mn in the Al-sensitive soybean (Glycine max) cultivar Jilin62. Results showed that more than 80% of the total cellular Al accumulated in the cell walls of the root tissue. Excessive Mn supply significantly increased the Al level in the root and aggravated Al toxicity, and as the result lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 43 publications
4
20
0
Order By: Relevance
“…and Mn toxicity. For instance, Yang et al (2009) found that excess Mn can increase the accumulation of Al 3? in soybean roots, and that high Al 3?…”
Section: Discussionmentioning
confidence: 99%
“…and Mn toxicity. For instance, Yang et al (2009) found that excess Mn can increase the accumulation of Al 3? in soybean roots, and that high Al 3?…”
Section: Discussionmentioning
confidence: 99%
“…Root elongation is also inhibited under water stress, but there are two main differences between Al and drought stress: (i) under drought stress shoot growth is much more affected than root growth (reviewed by , whereas short and medium-term Al excess may strongly reduce root growth without affecting shoot growth (Kochian et al 2004;Yang et al 2009); (ii) Al toxicity reduces cell elongation along the entire elongation zone (Kollmeier et al 2000), whereas under water deficit or osmotic stress cell elongation is inhibited only in the basal and central elongation zones (definition of zones according to Ishikawa and Evans 1993), but maintained toward the root apex (Sharp et al 1988) in the distal and apical elongation zones (Shimazaki et al 2005) (Fig. 1).…”
Section: Root-growth Response Of Plants To Aluminium Toxicity and Dromentioning
confidence: 99%
“…However, in natural soilplant systems, plants often have to face multiple metal stresses, and the interactive effects of two or more elements may be far from additive . Interaction of toxic metals can affect growth, biomass and photosynthesis of plants, such as Al and Cd in barley (Guo et al 2004) and soybean (Shamsi et al 2008), Cd and As in Solanum nigrum (Sun et al 2008), Al and Mn in soybean (Yang et al 2009), and Cd and Cr in Dalbergia sissoo (Shah et al 2008). However, the knowledge about concurrent behavior of Al and Cr is still scarce.…”
Section: Introductionmentioning
confidence: 99%